Changes of liver stiffness measured by magnetic resonance elastography during direct‐acting antivirals treatment in patients with chronic hepatitis C. Issue 6 (28th September 2020) - Higuchi, Mayu; Tamaki, Nobuharu; Kurosaki, Masayuki; Inada, Kento; Kirino, Sakura; Yamashita, Koji; Hayakawa, Yuka; Sekiguchi, Shuhei; Osawa, Leona; Takaura, Kenta; Maeyashiki, Chiaki; Kaneko, Shun; et al.
Abstract: Almost all patients achieved sustained virological response (SVR) by direct‐acting antivirals (DAA) therapy, but it is not clear as to what extent DAA therapy affects changes in liver fibrosis after achieving SVR. In this study, we investigated the changes of liver stiffness by magnetic resonance elastogaraphy (MRE) during DAA therapy. A total of 308 patients were enrolled in the study. Liver stiffness was measured twice before and after DAA treatment using MRE and time‐course change of liver stiffness was investigated. The median (interquartile range) values for liver stiffness were 4.2 (3.2–6.1) kPa at baseline and 3.3 (2.6–4.8) kPa at SVR, demonstrating a significant improvement ( p  < .01). A total of 44% of patients had no improvement in liver stiffness despite achieving SVR. In patients with advanced fibrosis (lower level of albumin [Alb] or histological fibrosis stage F4), it was difficult to improve liver stiffness. Except for Alb, there were no blood tests associated with nonimprovement in liver stiffness, making these cases difficult to predict. In conclusion, despite obtaining SVR, improvement in liver stiffness could not be obtained in some cases, especially in patients with advanced fibrosis. In these patients, liver stiffness must be followed even if SVR is obtained. Highlights: A total of 308 patients were received MRE before and after DAA therapy and changes in liver stiffness was examined. Liver stiffness significantly decreased after SVR in all patients, but 44% of patients had no improvement in liver stiffness. Improvement of liver stiffness was difficult to obtain in patients with advanced fibrosis (lower levels of albumin or histological fibrosis stage 4).